Polifonia, carnavalização e paródia na Teoria do Medalhão, de Machado de Assis: confronto com Le Père Goriot, de Balzac - Callipo, Daniela Mantarro [UNESP] (My University, 2014)
In the short story “Teoria do Medalhão”, written by Machado de Assis in 1881, a zealous father decides to give good advices to his son who just turned 21 years old. Using a speech that represents the official ideology of the eighteenth century, created by the dominant hegemony, including the France of Balzac’s time, the father suggests that the son abandons his ideals, using masks and annulling his thoughts and tastes to become a true Medalhão. The dialogue that is established between both of them is surrounded by irony and humor, because the father makes an apparently wise speech, which is, actually, empty and fool, leading to think about the concepts of parody and carnavalization by Bakhtin. Besides that, when he built a story in dialogue form, Machado de Assis transfers the word to the characters, in a crossing of voices that makes us think about “embryos” of polyphony. This work aims to make a bakhtiniana reading of the machadiano short story, “Teoria do Medalhão” in opposition to the novel Le Père Goriot by Balzac.

Em “Teoria do Medalhão”, escrito por Machado de Assis em 1881, um pai zeloso resolve dar bons conselhos a seu filho que acaba de completar 21 anos. Servindo-se de um discurso pertencente à ideologia oficial dos oitocentos, ou seja, aquela instituída pela hegemonia dominante, inclusive na França de Balzac, o pai sugere ao filho que abandone seus ideais, utilizando máscaras e anulando seus pensamentos e gostos, a fim de se tornar um verdadeiro Medalhão. O diálogo que se estabelece entre ambos é permeado de ironia e humor, pois o pai faz um discurso aparentemente sábio, mas que, na realidade, é vazio e tolo, levando a pensar nas noções de paródia e carnavalização de Bakhtin. Além disso, ao construir seu conto em forma de diálogo, Machado de Assis transfere a palavra às personagens, num cruzamento de vozes que leva a pensar em “embriões” de polifonia. Este trabalho visa, portanto, fazer uma leitura bakhtiniana do conto machadiano, contrapondo-o ao romance Le Père Goriot, de Balzac.
Polyphony, carnavalization and parody in the “Teoria do Medalhão”, by Machado de Assis: confrontation with Le Père Goriot, by Balzac
Keywords: Short story of Machado; Polyphony; Carnavalization; Parody; Le Père Goriot; Conto machadiano; Polifonia; Carnavalização; Paródia; Le Père Goriot